Which Value Supports Pro-environmental Behavior? Future Direction for Pre-service Physics Teacher (Unnes Science Education Journal, 2022)
Although a huge number of studies enhancing pro-environmental behavior (PEB), the environmental quality is still in poor condition. Enhancing PEB needs to consider some aspects, such as the value and location. Pre-service physics teachers have a role in shaping students’ PEB because environmental issues are part of the high school physics curriculum. This study aimed to investigate the link between the location, and values (biospheric, altruistic, egoistic, and hedonic), from two different locations in Indonesia. The modified and translated 2-MEV, and E-PVQ scales were used. This study concluded that the values in both locations are in the very high category, in which the values are correlated to PEB. The strongest correlated value is an egoistic value that is related to the self-enhancement indicating the need for self-enhance approaches in the class to promote PEB. The different locations which are in the same country didn’t show a significant difference in both values and PEB. Thus, future study could conduct their research in a larger area with a different culture to explore the relationship between PEB with location or other demographic aspects, and the development of activities to enhance PEB need to consider the strong relationship between PEB with egoistic value.